2016
DOI: 10.1016/j.cmet.2016.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Restriction Leads to Browning of White Adipose Tissue through Type 2 Immune Signaling

Abstract: SUMMARYCaloric restriction (CR) extends lifespan from yeast to mammals, delays onset of age-associated diseases, and improves metabolic health. We show that CR stimulates development of functional beige fat within the subcutaneous and visceral adipose tissue, contributing to decreased white fat and adipocyte size in lean C57BL/6 and BALB/c mice kept at room temperature or at thermoneutrality and in obese leptin-deficient mice. These metabolic changes are mediated by increased eosinophil infiltration, type 2 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
199
5
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(224 citation statements)
references
References 44 publications
16
199
5
4
Order By: Relevance
“…Several interventions have been described, which can reverse the phenotype of reduced mitochondrial function in WAT in obesity, the two most prominent examples being caloric restriction and treatment using PPARγ agonists [60]. Interestingly, this can be related to BAT as well, since PPARγ is considered one of the main regulators of BAT function as well as formation and since it was recently shown that caloric restriction induces BAT mass and functionality [61]. Taken together, it is tempting to speculate that the induction of a brown fat phenotype by the abovementioned interventions, which would result in an increased mitochondrial functionality, could be the reason for the observed beneficial effects on aging and metabolism.…”
Section: Impact Of Age On Mitochondria: Biogenesis Function Bioenermentioning
confidence: 99%
“…Several interventions have been described, which can reverse the phenotype of reduced mitochondrial function in WAT in obesity, the two most prominent examples being caloric restriction and treatment using PPARγ agonists [60]. Interestingly, this can be related to BAT as well, since PPARγ is considered one of the main regulators of BAT function as well as formation and since it was recently shown that caloric restriction induces BAT mass and functionality [61]. Taken together, it is tempting to speculate that the induction of a brown fat phenotype by the abovementioned interventions, which would result in an increased mitochondrial functionality, could be the reason for the observed beneficial effects on aging and metabolism.…”
Section: Impact Of Age On Mitochondria: Biogenesis Function Bioenermentioning
confidence: 99%
“…www.jlr.org Downloaded from eosinophils may be required for the WAT beiging in their models [16,31,73,74,115].…”
Section: Downloaded Frommentioning
confidence: 99%
“…To date, at least 10 primary research articles have examined the role of ILC2s in WAT homeostasis [14,16,31,94,95,112,113,115,117,119]. The initial studies used an RNase glycoprotein extracted from the Helminth egg to elicit weight loss and improve glucose tolerance associated with increased ILC2s, eosinophils, and M2-like macrophages [14].…”
Section: Ilc2s In Wat Type 2 Inflammation: Caveats and Controversiesmentioning
confidence: 99%
See 1 more Smart Citation
“…UCP1 is a hallmark of BAT, and recent studies have revealed that this protein is induced along with an increase in mitochondrial content in WAT during browning [53]. Moreover, accumulating studies have identified several other dominant transcriptional regulators of brown fat development and function, including PPARγ, PGC-1α, and PRDM16 [54]. PGC-1α is α major cofactor known to play a key role in mitochondrial biogenesis [50].…”
Section: Discussionmentioning
confidence: 99%